Staphylococcus aureus: setting its sights on the human innate immune system. Issue 4 (9th January 2019) - Buchan, Kyle D.; Foster, Simon J.; Renshaw, Stephen A.
Abstract : Staphylococcus aureus has colonized humans for at least 10 000 years, and today inhabits roughly a third of the population. In addition, S. aureus is a major pathogen that is responsible for a significant disease burden, ranging in severity from mild skin and soft-tissue infections to life-threatening endocarditis and necrotizing pneumonia, with treatment often hampered by resistance to commonly available antibiotics. Underpinning its versatility as a pathogen is its ability to evade the innate immune system. S. aureus specifically targets innate immunity to establish and sustain infection, utilizing a large repertoire of virulence factors to do so. Using these factors, S. aureus can resist phagosomal killing, impair complement activity, disrupt cytokine signalling and target phagocytes directly using proteolytic enzymes and cytolytic toxins. Although most of these virulence factors are well characterized, their importance during infection is less clear, as many display species-specific activity against humans or against animal hosts, including cows, horses and chickens. Several staphylococcal virulence factors display species specificity for components of the human innate immune system, with as few as two amino acid changes reducing binding affinity by as much as 100-fold. This represents a major issue for studying their roles during infection, which cannot be examined without the use of humanized infection models. This review summarizes the major factors S. aureus uses to impair the innate immune system, and provides an in-depth look into the host specificity of S. aureus and how this problem is being approached.